# Need help solving this problem. (Inverse Functions)

• Aug 9th 2011, 11:13 AM
bseymore
Need help solving this problem. (Inverse Functions)
Can anyone show me how to solve this?
g(x) = 10x^9 + 5x^3

10(g^-1(11))^9 + 5(g^-1(11))^3-9
• Aug 9th 2011, 11:14 AM
Siron
Re: Need help solving this problem. (Inverse Functions)
What do you have to solve? (I can't see anything, maybe I'm the only one)
• Aug 9th 2011, 11:18 AM
bseymore
Re: Need help solving this problem. (Inverse Functions)
i posted a screenshot of the problem but i guess it didnt work. i wrote it out above
• Aug 9th 2011, 12:11 PM
skeeter
Re: Need help solving this problem. (Inverse Functions)
Quote:

Originally Posted by bseymore
Can anyone show me how to solve this?
g(x) = 10x^9 + 5x^3

10(g^-1(11))^9 + 5(g^-1(11))^3-9

\$\displaystyle g(x) = 10x^9 + 5x^3\$

let \$\displaystyle a\$ be the real value such that \$\displaystyle g(a) = 11\$

since \$\displaystyle g(a) = 11\$ , \$\displaystyle g^{-1}(11) = a\$

\$\displaystyle 10a^9 + 5a^3 - 9 = g(a) - 9 = 11 - 9 = 2\$
• Aug 10th 2011, 10:48 AM
HallsofIvy
Re: Need help solving this problem. (Inverse Functions)
Quote:

Originally Posted by bseymore
Can anyone show me how to solve this?
g(x) = 10x^9 + 5x^3

10(g^-1(11))^9 + 5(g^-1(11))^3-9

For any (invertible) function g, \$\displaystyle g(g^{-1}(x))= x\$

Note that \$\displaystyle 10x^9+ 5x^3- 9= g(x)- 9\$.
• Aug 13th 2011, 05:41 AM
bseymore
Re: Need help solving this problem. (Inverse Functions)
thanks guys! I understand it now